The dual DPP4 inhibitor and GPR119 agonist HBK001 regulates glycemic control and beta cell function ex and in vivo - Yi Huan (Nature Portfolio, 2017)
Abstract Glucagon like peptide-1 (GLP-1) plays a vital role in glucose homeostasis and sustaining β-cell function. Currently there are two major methods to enhance endogenous GLP-1 activity; inhibiting dipeptidyl peptidase-4 (DPP4) or activating G protein-coupled receptor 119 (GPR119). Here we describe and validate a novel dual-target compound, HBK001, which can both inhibit DPP4 and activate GPR119 ex and in vivo. We show that HBK001 can promote glucose-stimulated insulin secretion in mouse and human primary islets. A single administration of HBK001 in ICR mice can increase plasma incretins levels much more efficiently than linagliptin, a classic DPP4 inhibitor. Long-term treatment of HBK001 in KKAy mice can ameliorate hyperglycemia as well as improve glucose tolerance, while linagliptin fails to achieve such glucose-lowing effects despite inhibiting 95% of serum DPP4 activity. Moreover, HBK001 can increase first-phase insulin secretion in KKAy mice, suggesting a direct effect on islet β-cells via GPR119 activation. Furthermore, HBK001 can improve islet morphology, increase β-cell proliferation and up-regulate genes involved in improved β-cell function. Thus, we have identified, designed and synthesized a novel dual-target compound, HBK001, which represents a promising therapeutic candidate for type 2 diabetes, especially for patients who are insensitive to current DPP4 inhibitors.